Exchange Rate Exposure and Its Determinants: A Firm and Industry Analysis of the UK Companies - He, Jiao (2010)
This study assesses whether the unexpected exchange rate movements volatilize the UK firms’ stock return based on the firm- and industry-level analysis, and examines whether the magnitude of the exchange rate exposure is determined by the firm-specific factors. Using a sample of 244 UK companies listed in the FTSE 350 during the test period between December 1999 and December 2009, the result documents that the exchange rate fluctuation does affect the firm value. Among the five introduced exchange rate indices, contemporaneous trade-weighted nominal exchange rate (TWN), equally-weighted exchange rate with major trade-partners (EQW), US$/UK£, EURO€ /UK£, and JP¥/UK£, the UK corporations are more subject to the TWN movements. In the whole, UK firms’ stock returns are positively related to the unexpected exchange rate movements, and about 78 percent of UK companies with significant exchange rate risk get benefits from the depreciation of the UK pound. In particular, domestic firms are proved to be more sensitive to the movements in the exchange rate than multinational corporations owing to the local competition. In addition, the findings provide strong evidence that there is a cross-sectional difference of exchange rate exposure across 26 industries-- Food Producer sector experiences the highest exchange rate risk and Pharmaceuticals & Biotechnology sector has the lowest exposure of exchange rate fluctuations. Consistent with initial expectation, the magnitude of the exchange rate exposure in the post-crisis period (2008-2009) is much higher that the pre-crisis period (2000-2007); this supports the plausible prospective that high volatility of the exchange rate caused by financial crisis erodes firm’ profitability. Pharmaceuticals & Biotechnology and Construction & Materials sectors tend to be stable before and after the crisis with the minimum changes in the exchange rate risk. Furthermore, by analysing the determinants of the exchange rate risk for individual companies, firms’ maturity, quick ratio and debt ratio are positively significant correlated with the degree of exchange rate risk, which means that firms with long established years, high liquidity ratios and high debt ratios, have low incentive to hedge, hence increase the exchange rate exposure. Firm size and dividend payout ratio, however, are positively and negatively insignificant related to the foreign currency risk, which may attribute to the initial data selection.